Intraosseous versus intravenous access in patients with out-of-hospital cardiac arrest: Insights from the resuscitation outcomes consortium continuous chest compression trial. (January 2019) - Mody, Purav; Brown, Siobhan P.; Kudenchuk, Peter J.; Chan, Paul S.; Khera, Rohan; Ayers, Colby; Pandey, Ambarish; Kern, Karl B.; de Lemos, James A.; Link, Mark S.; Idris, Ahamed H.
Abstract: Aim: To examine outcomes associated with intraosseous access route attempt for delivery of medications during out-of-hospital cardiac arrest (OHCA) resuscitation. Methods: Using data from the Continuous Chest Compression trial, we examined rates of survival to hospital discharge, sustained return of spontaneous circulation (ROSC), and survival with favorable neurological function among patients with intraosseous and intravenous access attempts after adjusting for age, sex, initial rhythm, bystander cardiopulmonary resuscitation, public location, witnessed status, EMS response and trial randomization cluster. Results: Among 19, 731 patients, intraosseous access was attempted in 3068 patients and intravenous access in 16, 663 patients respectively. Patients in whom intraosseous access was attempted were younger, more often female, and had marginally faster times to initial access and to initial drug administration. Unadjusted outcomes were significantly lower in patients with attempted intraosseous access compared with intravenous access: (4.6% vs. 5.7%, p = 0.01) for survival to discharge, (17.9% vs. 23.5%, p < 0.001) for sustained ROSC and (2.8% vs. 4.2%, p < 0.001) for survival with favorable neurological function. After adjustment, there were no differences in hospital survival (OR, 0.88, 95% CI 0.72–1.09, p = 0.24) or survival with favorable neurological function (OR, 0.87, 95% CI 0.67–1.12, p = 0.29) in patients with intraosseous access attempt (vs. intravenous access). However, intraosseous access continued to associate with lower rates of sustained ROSC (OR, 0.80, 95% CI 0.71 – 0.89, p < 0.001). Conclusions: Among patients with OHCA, intraosseous access attempt was associated with worse ROSC rates but no difference in survival. Further studies are necessary to elucidate the optimal access route among OHCA patients.